Hubungan Verbal Bullying dengan Kecerdasan Interpersonal Peserta Didik SD - Ahmad Fadhlilah; Ika Wulandari Utamining Tias (Universitas Lampung, 2020)
The problem in this research was the existence of verbal bullying behavior and its relation to the students’ interpersonal intelegence in fourth class Primary School state in Budi Utomo Cluster District Sub of Metro Selatan Metro City. This research aims to determine the significant relationship between verbal bullying with intellegence interpersonal students. This type of research is ex-postfacto correlation. The population is 78 students and all populations are used as research samples. The instrument for data collection is a questionnaire with a Likert scale, which was previously tested for validity and reliability. Data analysis used product moment correlation. Based on the analysis conducted by the results of the study it can be concluded that there is a positive and significant relationship between verbal bullying with intellegence interpersonal indicated by a correlation coefficient at the level of